A Baby Clinic in an Elementary School: Towards an Integration of School, Family, and Community Life - Allan, John (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes how a public health nurse establisheda baby clinic in an elementary school and the effects it had on family, school,and community life. It will be shown how the nurse responded to the lackof community facilities for young mothers by encouraging the mothers todevelop their own program, how the 6th and 7th graders became involved,and the role of the counsellor. It is hoped that in sharing such an experienceothers may be encouraged to devise and implement their own models.